In vitro diagnostics of coronavirus disease 2019: Technologies and application - Lai, Chih-Cheng (J Microbiol Immunol Infect, 2021)
Laboratory-based diagnostic measures including virological and serological tests are essential for detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Real-time reverse transcription-polymerase chain reactions (rRT-PCR) can detect SARS-COV-2 by targeting open reading frame-1 antibodies (ORF1ab), envelope protein, nucleocapsid protein, RNA-dependent RNA polymerase genes, and the N1, N2, and N3 (3N) target genes. Therefore, rRT-PCR remains the primary method of diagnosing SARS-CoV-2 despite being limited by false-negative results, long turnaround, complex protocols, and a need for skilled personnel. Serological diagnosis of coronavirus disease 2019 (COVID-19) is simple and does not require complex techniques and equipment, rendering it suitable for rapid detection and massive screening. However, serological tests cannot confirm SARS-CoV-2, and results will be false-negative when antibody concentrations fall below detection limits. Balancing the increased use of laboratory tests, risk of testing errors, need for tests, burden on healthcare systems, benefits of early diagnosis, and risk of unnecessary exposure is a significant and persistent challenge in diagnosing COVID-19.